Complement-Dependent Mechanisms and Interventions in Periodontal Disease - Hajishengallis, George; Kajikawa, Tetsuhiro; Hajishengallis, Evlambia; Maekawa, Tomoki; Reis, Edimara S.; Mastellos, Dimitrios C.; Yancopoulou, Despina; Hasturk, Hatice; Lambris, John D. (Frontiers in Immunology, 2019)
Periodontitis is a prevalent inflammatory disease that leads to the destruction of the tooth-supporting tissues. Current therapies are not effective for all patients and this oral disease continues to be a significant public health and economic burden. Central to periodontal disease pathogenesis is a reciprocally reinforced interplay between microbial dysbiosis and destructive inflammation, suggesting the potential relevance of host-modulation therapies. This review summarizes and discusses clinical observations and pre-clinical intervention studies that collectively suggest that complement is hyperactivated in periodontitis and that its inhibition provides a therapeutic benefit. Specifically, interception of the complement cascade at its central component, C3, using a locally administered small peptidic compound (Cp40/AMY-101) protected non-human primates from induced or naturally occurring periodontitis. These studies indicate that C3-targeted intervention merits investigation as an adjunctive treatment of periodontal disease in humans.